Interlaminar Tension-Tension Fatigue of Woven Glass Fiber Reinforced Plastic Composite Laminates at Low Temperatures - Narita, Fumio; Tanaka, Chieko; Suzuki, Masashi (Journal of Composites and Biodegradable Polymers, 2018)
Experimentally characterizing the through-thickness tensile behavior of composite laminates is challenging. This paper investigates the through-thickness tensile fatigue behavior of woven glass fiber reinforced plastic (GFRP) composite laminates at low temperatures. Cyclic through-thickness tensile tests were performed with cross specimens at room temperature and liquid nitrogen temperature (77 K), and the maximum interlaminar stress versus number of cycles to failure (S-N curve) was evaluated. The interlaminar tensile fatigue mechanisms of the woven GFRP composite laminates at low temperatures were also discussed. It was shown that resin fracture is dominant at room temperature, and the interface bonding fracture between the fiber and the matrix is dominant at 77K.